2019
DOI: 10.1126/scitranslmed.aas9917
|View full text |Cite|
|
Sign up to set email alerts
|

Antimalarial pantothenamide metabolites target acetyl–coenzyme A biosynthesis in Plasmodium falciparum

Abstract: Malaria eradication is critically dependent on new therapeutics that target resistant Plasmodium parasites and block transmission of the disease. Here, we report that pantothenamide bioisosteres were active against blood-stage Plasmodium falciparum parasites and also blocked transmission of sexual stages to the mosquito vector. These compounds were resistant to degradation by serum pantetheinases, showed favorable pharmacokinetic properties, and cleared parasites in a humanized mouse model of P. falciparum inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 55 publications
3
99
0
Order By: Relevance
“…It is important to note that the metabolomics experiments in this study were exploratory in nature, involving one to two biological replicates to screen for known and novel candidate mode of actions within a large set of compounds. Once compounds are selected and prioritized for further discovery or development studies, these metabolomics data should be complemented with targeted in-depth follow-up studies to validate candidate targets and mode of actions as demonstrated recently for a new class of pantothenamides (Schalwijk et al, 2019).…”
Section: Figure 7 Metabolic Profiling Of Compounds Identified Cellular Processes Targeted By Compoundsmentioning
confidence: 99%
“…It is important to note that the metabolomics experiments in this study were exploratory in nature, involving one to two biological replicates to screen for known and novel candidate mode of actions within a large set of compounds. Once compounds are selected and prioritized for further discovery or development studies, these metabolomics data should be complemented with targeted in-depth follow-up studies to validate candidate targets and mode of actions as demonstrated recently for a new class of pantothenamides (Schalwijk et al, 2019).…”
Section: Figure 7 Metabolic Profiling Of Compounds Identified Cellular Processes Targeted By Compoundsmentioning
confidence: 99%
“…In the whole CoA biosynthetic pathway, PfPanK has been best studied in P. falciparum (Saliba et al, 1998;Spry et al, 2008). All inhibitors against PfPanK that were so far identified are structurally related to pantothenate, including pantothenamide metabolites (Schalkwijk et al, 2019), pantothenol (PanOH), and CJ-15,801 Spry et al, 2005). Although these potential pantothenate analogs were presumed to target the CoA pathway, they apparently showed no direct inhibition against PfPanK and likely inhibit other targets such as PfPPCS and CoA-utilizing enzymes (Tjhin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PptT inhibitors such as 8919 (82) (Ballinger et al, 2019), and inhibitors of enzymes involved in the glyoxylate shunt (such as isocitrate lyase, ICL) should both work synergistically with compounds reducing CoA levels (Wellington and Hung, 2018). This should also be the case for pantothenamides that are converted to CoA antimetabolites that target CoA utilizing enzymes (as seems to be the case in the malaria parasite, Plasmodium falciparum) (Schalkwijk et al, 2019). Considering that combination treatments have been the mainstay of antiTB drug regimens, multi-target inhibitors that all have a CoA producing or utilizing enzyme in the crosshairs could prove to be the breakthrough that is so urgently needed in the development of new antiTB drugs.…”
Section: Resultsmentioning
confidence: 99%